1983
DOI: 10.1016/0014-5793(83)81120-x
|View full text |Cite
|
Sign up to set email alerts
|

Three kinds of extracellular glucosyltransferases from Streptococcus mutans 6715 (serotype g)

Abstract: In addition to the 1,3*-D-glucan synthetase (p1 4.9) and the highly-branched 1,6_cu-D-glucan synthetase (PI 3.9-4.1), Streptococcus mutans 6715 (serotype g) was found to secrete the third glucosyltransferase in multiple forms (PI 5.5-7.0), which exhibited 87% 1,6_cu-bond-, 6% 1,3_cu-bond-and 7% 1,3,6-branchforming activities. The production of this enzyme was extremely enhanced when the organism was grown in Tween IO-supplemented medium. The 3 glucosyltransferases from the same organism were enzymatically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 19 publications
2
57
0
Order By: Relevance
“…Although several investigators have found that S. sobrinus secretes only three kinds of GTF (9,13,19), we have reported that strain AHT-k of S. sobrinus secretes four kinds of GTF (20). These types were separated by DEAE-cellulose column chromatography; and the four GTFs were then designated P1, P2, P3, and P4 by their order of elution from the DEAE-cellulose column.…”
mentioning
confidence: 95%
“…Although several investigators have found that S. sobrinus secretes only three kinds of GTF (9,13,19), we have reported that strain AHT-k of S. sobrinus secretes four kinds of GTF (20). These types were separated by DEAE-cellulose column chromatography; and the four GTFs were then designated P1, P2, P3, and P4 by their order of elution from the DEAE-cellulose column.…”
mentioning
confidence: 95%
“…This activity is dependent upon the production of extracellular glucosyltransferases (GTF; EC 2.4.1 .5) which synthesize water-insoluble adherent glucans from sucrose. An examination of different strains of mutans streptococci has revealed two different classes of GTF : GTF-I, which synthesizes primarily water-insoluble glucans and GTF-S, which synthesizes predominantly water-soluble glucans (Kuramitsu & Wondrack, 1983;Shimamura et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories have isolated and characterized these two types of GTFs (6,15,20). In fact, one organism related to S. mutans, Streptococcus sobrinus 6715, appears to produce three distinct GTFs (21).…”
mentioning
confidence: 99%